Influência da adubação fosfatada e calagem sobre a absorção do zinco, em dois solos de Minas Gerais - G F T Castro Bahia, Francisco; Braga, José Mário (Revista Ceres, 2025)
Two experiments were installed in the greenhouse to study the relationships between phosphate fertilization, liming and zinc fertilization. One experiment used a red latosol soil while the other used a dark brown acid soil. Hybrid corn ’AG 206’ was used to plant both experiments.